Perbandingan Penerimaan Pajak Sektor Pariwisata Sebelum dan Sesudah Krisis Kesehatan Global - Martian, Catur; Tunisa, Indri Rahmat (Jurnal Kajian Pariwisata, 2025)
The period of crisis posed a serious threat across various regions of Indonesia, affecting not only public health but also the stability of the national economy. The continuous surge in cases compelled the government to implement strategic measures through the enactment of Social Restriction policies. Although aimed at safeguarding public health, these measures inadvertently led to a slowdown, and in some cases, a temporary halt in numerous economic activities. The impact of these policies was particularly evident in the tourism sector, which experienced a significant decline in its contribution to regional tax revenues—especially from hotel, restaurant, and entertainment taxes. This study aims to evaluate and compare the significant differences in tax revenues from these three business sectors before and after the crisis. Using a quantitative approach with a comparative method, the study processes numerical data, which is then statistically analyzed to obtain an objective and accurate overview. The results of the analysis reveal a substantial difference in the amount of tax revenue from hotels, restaurants, and entertainment businesses between the pre-crisis and post-crisis periods, highlighting the considerable impact of the crisis on these sectors